2014
DOI: 10.1002/jsfa.7009
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy application in frozen carrot cooked in different ways and the relationship with carotenoids

Abstract: BACKGROUND: Raman spectroscopy, in its confocal micro-Raman variation, has been recently proposed as a spatially resolved method to identify carotenoids in various food matrices, being faster, non-destructive, and avoiding sample extraction, but no data are present in the literature concerning its application to the evaluation of carotenoid pattern changes after thermal treatment of carrots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 32 publications
4
10
0
Order By: Relevance
“…The reduction of b *, in comparison to the raw sample, was more visible for the longer cooking times. The decrease of L * indicates darkening, while the reduction of both a* and b * indicates a general colour loss, as already reported for cooked carrots . These observations may be related to a decrease and/or isomerisation of α ‐ and β ‐carotene, the orange pigments of which the pumpkin is rich, as previously reported by other authors …”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The reduction of b *, in comparison to the raw sample, was more visible for the longer cooking times. The decrease of L * indicates darkening, while the reduction of both a* and b * indicates a general colour loss, as already reported for cooked carrots . These observations may be related to a decrease and/or isomerisation of α ‐ and β ‐carotene, the orange pigments of which the pumpkin is rich, as previously reported by other authors …”
Section: Resultssupporting
confidence: 82%
“…reported a 9.5% increase of the total carotenoids extractability in pumpkin steamed for 5 min, in comparison to the raw ones. The higher a * and b * values of the steamed samples may be thus related to the extended extractability of this molecules, as already reported for carrots . The lower colour parameters of the air–steam cooked samples in comparison to the control, even at the same time and temperature conditions, suggest, also in this case, an extended oxidation due to the air.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Nonenzymatic browning usually lead to darkening on vegetables and fruits, which is reflected in the significant decrease of L* values ( p < .05). The reduction of L*, a*, and b* after thermal process was already reported by previous researchers, which was result from oxidation and isomerization of β‐carotene (Camorani et al, ). HHP could maintain color characteristics much better than blanching, shown as a significant difference in L*, a*, and b* between heat and HHP group.…”
Section: Resultssupporting
confidence: 64%
“…Thus, steaming was the cooking method that more drastically affected the colour of frozen carrots. Recently, Camorani et al (2015) found that frozen carrots cooked under the same conditions used in this study exhibited carotenoids isomerisation with a significant increase in cis-β-carotene form. High correlations were found among all colour parameters and the ratio cis/all-trans-β-carotene, confirming the influence of the carotenoids isomerisation, as induced by heat treatment, on the final colour of the samples.…”
Section: Colour Characteristicsmentioning
confidence: 55%